Verbal Helper Application for Autism using Natural Language Processing / Nur Farahin Mohd Affendy - Mohd Affendy, Nur Farahin (2020)
Autism can make communicating and associating with others difficult for a child. Autistic child tends to live in their own world which they do not socialize with others. Therefore, they are experiencing verbal issues. Autism is a neuro-developmental conditions which makes them behave repetitive tasks. A Recurrent Neural Network (RNN) was used in this project to predict next possible word until it becomes a sentence. Furthermore, N-gram also used for grammar checking for a simple sentence. The prediction words are displayed based on the frequency of the word chosen. This application results a valid sentence generated or chosen by autistic child to ease them communicating with others. Moreover, it helps caretaker or parents to teach them on how to express verbally after this. Thus, this application might be used for autistic children to help them express verbally.